2011
DOI: 10.1186/1471-2229-11-155
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function mutations affecting a specific Glycine max R2R3 MYB transcription factor result in brown hilum and brown seed coats

Abstract: BackgroundAlthough modern soybean cultivars feature yellow seed coats, with the only color variation found at the hila, the ancestral condition is black seed coats. Both seed coat and hila coloration are due to the presence of phenylpropanoid pathway derivatives, principally anthocyanins. The genetics of soybean seed coat and hilum coloration were first investigated during the resurgence of genetics during the 1920s, following the rediscovery of Mendel's work. Despite the inclusion of this phenotypic marker in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 55 publications
5
69
0
Order By: Relevance
“…Based on a combined analysis of transcriptome and metabolome data, another recent study identified 20 anthocyanin, flavonoid and phenylpropanoid isogenes that were differentially expressed between black ( iRT ) and brown ( irT ) seeded soybean isolines [5]. This same study suggested that R locus candidate might be a transcription factor at the distal end of chromosome Gm09 at or near Glyma09g36840, 120 kb from the Glyma09g36983 MYB factor mapped by Gillman et al [4].…”
Section: Introductionmentioning
confidence: 94%
“…Based on a combined analysis of transcriptome and metabolome data, another recent study identified 20 anthocyanin, flavonoid and phenylpropanoid isogenes that were differentially expressed between black ( iRT ) and brown ( irT ) seeded soybean isolines [5]. This same study suggested that R locus candidate might be a transcription factor at the distal end of chromosome Gm09 at or near Glyma09g36840, 120 kb from the Glyma09g36983 MYB factor mapped by Gillman et al [4].…”
Section: Introductionmentioning
confidence: 94%
“…An R1 MYB transcription factor, GmMYB176, regulates CHS8 expression and isoflavonoid synthesis in soybean (Yi et al, 2010). A loss-of-function mutation in a specific R2R3 MYB transcription factor gene (Glyma09g36990) in soybean resulted in a brown hilum and brown seed coat (Gillman et al, 2011). GmMYB-G20-1 is a candidate gene for the W2 locus, which generates a purple-blue color and a high vacuolar pH in soybean flower petals (Takahashi et al, 2011;Takahashi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are 244 typical R2R3-MYB proteins in a primary soybean genome data set (Du et al, 2012). However, only 12 members of the MYB family have been functionally characterized, thus far, in soybean (Miyake et al, 2003;Yang, 2007;Liao et al, 2008;Du et al, 2008;Libault et al, 2009;Yi et al, 2010;Gillman et al, 2011;Takahashi et al, 2011). The functions of most plant MYB genes are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One recessive gene conditioning the phenotype spread hilum in the T48 genotype was found. The expression of the spread hilum is dependent of locus T_, which controls pubescence color; therefore it occurs only in genotypes with brown pubescence (T_), which characterizes pleiotropic effect of this locus on the trait spread hilum [10].…”
Section: Introductionmentioning
confidence: 99%
“…More recently Gillman et al [10] identified the specific gene and causative basis behind the phenomenon of brown hilum/seed coat coloration in soybean (R locus), and discovered an allelic series of four loss of function mutations affecting our R locus gene candidate (R 2 R 3 MYB gene). The presence of each one of these mutations was perfectly correlated with the brown seed coat/hilum phenotype in a broadly distributed survey of soybean cultivars.…”
Section: Introductionmentioning
confidence: 99%